Slang Words in Twenty One and Over - Abdah; Fikriani Aminun Omolu; Sahril (Universitas Muhammadiyah Palu, 2023)
This research aims at identifying the slang words in the movie Twenty One and Over. It also aims at defining the meaning and classifying types of slang words. This research is a qualitative descriptive method. The data source of the research is the researchers themselves and the movie Twenty One and Over. As a result, the researchers found that there are slang words often used in the movie. Each slang word has its meaning, described in this article. Those slang words are classified into three types of slang. They are society slang, workmen's slang, and public house slang.